2017
DOI: 10.1101/149237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serology reflects a decline in the prevalence of trachoma in two regions of The Gambia

Abstract: Trachoma is caused by Chlamydia trachomatis (Ct). It is targeted for global elimination as a public health problem. In 2014, a population-based cross-sectional study was performed in two previously trachoma-endemic areas of The Gambia. Participants of all ages from Lower River Region (LRR) (N = 1028) and Upper River Region (URR) (N = 840) underwent examination for trachoma and had blood collected for detection of antibodies against the Ct antigen Pgp3, by ELISA. Overall, 30 (1.6%) individuals had active tracho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Our investigation builds upon an existing body of work characterizing the dynamics between clinical, serological, and molecular trachoma indicators. Reports at the district, village, and individual level have established that relatively high levels of clinical trachoma or ocular infections tend to correspond to higher seroprevalence and/or seroconversion rates (14, 28-31); post-elimination settings have been of particular interest, with populations often displaying little to no antibody response (15,(32)(33)(34)(35)(36)(37). Our findings align with earlier studies that showed clinical trachoma is more strongly correlated with infection prevalence in populations with ongoing transmission compared to populations in which transmission has been suppressed by MDA (38)(39)(40); also in agreement with prior findings, we observed that TI was slightly, but not significantly, more closely correlated with infection prevalence compared to TF immediately following MDA (Figure S10) (41).…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation builds upon an existing body of work characterizing the dynamics between clinical, serological, and molecular trachoma indicators. Reports at the district, village, and individual level have established that relatively high levels of clinical trachoma or ocular infections tend to correspond to higher seroprevalence and/or seroconversion rates (14, 28-31); post-elimination settings have been of particular interest, with populations often displaying little to no antibody response (15,(32)(33)(34)(35)(36)(37). Our findings align with earlier studies that showed clinical trachoma is more strongly correlated with infection prevalence in populations with ongoing transmission compared to populations in which transmission has been suppressed by MDA (38)(39)(40); also in agreement with prior findings, we observed that TI was slightly, but not significantly, more closely correlated with infection prevalence compared to TF immediately following MDA (Figure S10) (41).…”
Section: Discussionmentioning
confidence: 99%
“…Serologic testing for antibody responses against C. trachomatis antigens is gaining traction as a potential approach for conducting surveillance in areas that have achieved elimination criteria for trachoma and ceased interventions. Seroprevalence of anti-C. trachomatis antibodies typically increases with age among 1to 9-year-olds in areas with ongoing transmission [10][11][12] but remain relatively flat, with low seroconversion rates, 13 in the absence of transmission [14][15][16] and in settings where the presence of TF does not correlate with ocular C. trachomatis infection. 17,18 Serologic testing is standard for yaws diagnosis: the T. pallidum particle agglutination (TPPA) assay reflects a history of T. pallidum infection, whereas nontreponemal tests such as rapid plasmin reagin (RPR) detect antibodies against host molecules released in response to infection, giving an indication of current or recent exposure.…”
Section: Introductionmentioning
confidence: 99%